Pengembangan Media Belajar IPA Berbasis Power Point Interaktif - Rista Hardiyanti; Ahmad Gawdy Prananosa; Dedy Firduansyah (Journal of Elementary School (JOES), 2023)
This research aims to develop interactive power point-based media design. To test validity, practicality and effectiveness of interactive power point-based learning media in science learning at SD Negeri 56 Lubuklinggau. This type of research is Research and Development with a 4-D development model. The subject of this research is the fifth grade students of SD Negeri 56 Lubuklinggau. Data collection techniques use interviews, observations, questionnaires, tests and documentation. Based on the results of validation of interactive power point-based learning media based on the assessment of linguists, materials and media show that interactive powerpoint-based learning media meets the valid criteria with an average score of 0,83. Meanwhile, From the analysis of the teacher and student practicality assessment sheets it was found that interactive powerpoint-based learning media met the practical criteria score 91,5%. In the field test, the N-gain (g) of 0,67 was media has moderate classification, which means that interactive powerpoint-based learning media has moderate effectiveness. Based on the results of study it can be concluded that interactive powerpoint-based learning media is proven to be valid, practical, and has effective in learning science at SD Negeri 56 Lubuklinggau. Keywords: Development, Power Point, Interactive, IPA, Elementary School.